PENGARUH KOMPETENSI, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI - La Ode Hasan Idris; Samdin Samdin; La Ode Kalimin (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
This study intends to analyze the simultaneous and partial effect of competence, work discipline and work environment on employees performance in the Southeast Sulawesi Provincial Forestry Service.The population of this research was the Civil Servants (PNS) of the Provincial Forestry Service of Southeast Sulawesi. The size of the sample in this research was determined by using the Slovin formula which amounted to 96 respondents. The determination of this research sample used probability sampling techniques, which is proportional stratified random sampling. Strata was carried out based on the placement of employees of the Provincial Forestry Service of the Southeast Sulawesi. The method of collecting data was using questionnaires and literature review. The analytical tool used is the Multivariate Regression Analysis (MRA) using SPSS for Windows 24.0.The result of the research shows: 1) competence, work discipline and work environment simultaneously have positive and significant effects on employee performance; 2) competence has positive and significant effects on employees performance; 3) work discipline has positive and significant effects on employees performance; and 4) work environment has positive and insignificant effects on employees performance.Keywords: competence, work discipline, work environment and employees performance